2006
DOI: 10.1073/pnas.0600331103
|View full text |Cite|
|
Sign up to set email alerts
|

Brain response to putative pheromones in lesbian women

Abstract: The progesterone derivative 4,16-androstadien-3-one (AND) and the estrogen-like steroid estra-1,3,5(10),16-tetraen-3-ol (EST) are candidate compounds for human pheromones. In previous positron emission tomography studies, we found that smelling AND and EST activated regions primarily incorporating the sexually dimorphic nuclei of the anterior hypothalamus, that this activation was differentiated with respect to sex and compound, and that homosexual men processed AND congruently with heterosexual women rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
137
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(143 citation statements)
references
References 52 publications
3
137
1
2
Order By: Relevance
“…Apparently heterosexual men are not stimulated by a male scent, which suggests that pheromones contribute to determining our behavior in relation to our sexual orientation (125). In a follow-up study (126), lesbian women, as compared to heterosexual women, reacted in a sexatypical, almost reciprocal way to pheromones. These observations, too, show that there are hypothalamic circuits that function in a way that depends on our sexual orientation.…”
Section: Sexual Orientation and The Brainmentioning
confidence: 97%
“…Apparently heterosexual men are not stimulated by a male scent, which suggests that pheromones contribute to determining our behavior in relation to our sexual orientation (125). In a follow-up study (126), lesbian women, as compared to heterosexual women, reacted in a sexatypical, almost reciprocal way to pheromones. These observations, too, show that there are hypothalamic circuits that function in a way that depends on our sexual orientation.…”
Section: Sexual Orientation and The Brainmentioning
confidence: 97%
“…In male homosexuals, regions of the brain that are associated with sexual activity activate in response to a testosterone derivative with pheromone-like properties [63]. An estrogen derivative similarly activated the same brain regions in homosexual women [64]. The responses are sex atypical, and researchers have begun to attribute such differences to anatomical features of the brain, for example amygdala connections, that are differentiated with respect to sexual orientation but not biological sex [65].…”
Section: Box 2 Insights From Studies Of Human Homosexual Orientationmentioning
confidence: 99%
“…Pheromones thus may play a part in our behavior related to sexual orientation. A follow-up study (3) showed that HoW reacted in a sex-atypical, almost reciprocal, way to pheromones as compared with HeW, again indicating that some hypothalamic circuits function in relation to sexual orientation. Kranz and Ishai (11) expanded this observation to cortical areas.…”
mentioning
confidence: 95%
“…This sexual differentiation process is accompanied by many structural and functional brain differences among these groups (1). In previous studies (2,3), the Savic laboratory detected a sex-differentiated activation of the anterior hypothalamus in heterosexual men (HeM) and heterosexual women (HeW) and a sex-atypical, almost reversed, pattern of activation in homosexual men (HoM) and homosexual women (HoW). The hypothalamus (Fig.…”
mentioning
confidence: 96%